Obtención potencial de polímeros biodegradables. Estudio de la disolución de la cáscara de piña en PEG (ING) - Moya P., Manuel (1995)
The conditions to dissolve pineapple peel in Polyethylenglycol 400 were determined. The conditions are: particle size between 125 and 150 micrometers, relation substratum/PEG 1:1, temperature 225°C and dissolution time 3 hours.Analysis of the solution yielded [OH]= 3,6 ± 0,2 mmol/g, [COOH]= 1,10 ± 0,03 mmol/g ,  and water content 2,70 ± 0,05 mg/mL.